Twenty years of femicide in Milan: A retrospective medicolegal analysis. Issue 2 (March 2022) - Biehler-Gomez, Lucie; Maggioni, Lidia; Tambuzzi, Stefano; Kustermann, Alessandra; Cattaneo, Cristina
Highlights: A 20-year medico-legal retrospective study of femicide cases in Milan. Perpetrators are for the most part intimate/ex-intimate partners. Femicides most frequently occur in the domestic setting. Women under 50 years of age are mostly killed by sharp force trauma. Women over 50 years of age are mostly killed by blunt force trauma. Abstract: Femicide constitutes a leading cause of premature deaths for women, yet it has been the subject of limited research until recently. Enhanced data collection and analysis on killings of women and girls are necessary to understand and address this unrelenting phenomenon. This study examines all cases of female homicide encountered at the Institute of Legal Medicine of Milan (Italy) spanning from 1999 to 2019; data from 2020/2021 were shown separately given the bias that the forced cohabitation and stay at home during the lockdowns of the SARS-CoV-2 pandemic may represent regarding violence against women and femicide. In this study, specific factors were considered, including the age and nationality of the victims, the place of recovery of the bodies, the victim's relationship to the perpetrator and the injuries they suffered. As a result, 200 female killings were found among the over 15, 000 autopsies and 535 homicides investigated at the Institute of Legal Medicine of Milan from 1999 to 2019, representing an average of 9.5 femicides yearly. The majority of victims were Italian (74%) and half were aged between 18 and 49 years old. The killings were overwhelmingly committed in the domestic setting (78.5%) by male perpetrators (at least 85%), related to the victims as intimate or ex-intimate partners and members of the family (73.5%). The homicides were mainly perpetrated with sharp (32%) or blunt instruments (21.5%), shooting (18.5%) and asphyxiation (16.5%). This study is part of a growing effort to enhance data collection and analysis on femicide. Studying and monitoring the rates of femicide (or "femicide watch") will permit to better understand, reduce, and finally end femicide globally.